Deskripsi Business Model Canvas Usaha Minyak Serai Wangi Di Desa Pinilih Kecamatan Dimembe Kabupaten Minahasa Utara - Tarigan, Adriana Br; Loho, Agnes Estephina; Pangemanan, Lyndon Reindhart Jacob (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2024)
This study aims to describe the business model of citronella oil business in terms of Business Model Canvas in Pinilih Village, Dimembe District, North Minahasa Regency. This research was conducted for three months starting from May to July 2023 at the citronella oil business in Pinilih Village, Dimembe District, North Minahasa Regency. Data analysis used in this study used the Business Model Canvas approach. Data collection techniques using interviews and observations. The research data collected were primary data and secondary data. The results of this study are a description of the business model of the citronella oil business obtained from the nine elements of the business model canvas to maintain product quality, utilize technological advances by creating social media sarimbata business, improve service quality, marketing activities for the citronella oil business. It is hoped that this research can provide benefits to increase revenue streams and develop businesses so that they can compete in the future.